PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN UKURAN KAP TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN SEKTOR KEUANGAN SUB SEKTOR BANK - Muhammad Yahya; Usep Siswadi; Nurhaini (The Asia Pacific Journal Of Management Studies, 2024)
Financial reports are communication tools that contain information made by company management in the form of financial data whose contents are about transactions within a company that occur during a certain period. Timeliness in the submission of financial statements is very important for parties with an interest in financial statements. Timeliness means the availability of information for decision makers at the right time so that it can influence their decisions. The population taken as the object of this research is 47 companies in the financial sector sub-sector of banks listed on the IDX during the period 2017-2021. quantitative data used in the form of secondary data. Determination of the sample using purposive sampling method and obtained a sample of 15 companies. Data were analyzed using multiple linear regression model using SPSS version 26 program.The results of the partial study using the t-test showed that the two independent variables that showed an influence on the Audit Report Lag were the firm size variable with a significance value of 0.014 less than 0.05, and the KAP size variable with a significance value of 0.000 less than 0.05 while the Profitability variable was not. has an influence on the Audit Report Lag because it has a significance value greater than 0.05, which is 0.128. Based on the F test, simultaneously Profitability, Company Size, and KAP Size affect the Audit Report Lag because it has a significance value of less than 0.05, which is 0.000 and has an influence relationship of 54.7% seen from the results of the Coefficient of Determination (R Square), the remaining 45.3% is influenced by other variables not examined in this study.